Potencial de Trichogramma pretiosum (hymenoptera: trichogrammatidae) visando ao manejo de Trichoplusia ni (lepidoptera:noctuidae) - Altoé, Thiago da Silva (2009)
This research had the objective to study the biology and determine the thermal exigencies of Trichogramma pretiosum reared on Trichoplusia ni eggs, in temperatures of 18, 21, 24, 27, 30, 33°C and the parasitism capacity on the ideal temperature as well. T